Effectiveness of Using Household Liquid Waste For Biogas Production With Anaerobic Fermentation - A. Farihah Manggabarani; Nurjannah; Takdir Syarif (International Journal of Science and Environment (IJSE), 2026)
This study examined the effectiveness of utilizing household wastewater as asubstrate for biogas production through anaerobic fermentation at ahousehold scale in Tobarakka Village, Pitumpanua District. The objectives ofthe study were to assess the ability of various types of wastewater (ricewashing, vegetable waste, and a mixture) to produce biogas and to modeltheir production kinetics. Samples were processed in a simple biodigester(household-scale plastic bottles) and gas production was measuredperiodically using the air displacement method; data were analyzed statistically (ANOVA / LMM) and modeled with the Modified Gompertzequation. The results showed that biogas production per interval decreasedover time but the 40-day accumulation was highest in the mixture treatment(450 mL), followed by rice washing (355 mL) and vegetable waste (135 mL).Changes in pH and mesophilic conditions (≈30–35 °C) were noted to supportmethanogenic activity even though the final pH was close to the loweroptimal limit. The ANOVA/LMM test indicated that the effect of time washighly significant (p < 0.001), the effect of treatment was approaching significance (p ≈ 0.050), and the Treatment×Time interaction was significant(p = 0.028), suggesting different production patterns between substrates overtime.Modified Gompertz modeling confirmed the mixture as the substrate withthe highest cumulative potential and production rate. Limitations include thesmall number of replicates (n = 3) and the lack of gas composition analysis(%CH₄, %CO₂, H₂S) and VFA/COD parameters; therefore, additionalreplicates, gas composition measurements, and mixing ratio optimization arerecommended for further research. Practically, the utilization of household liquid waste, especially in combination, has the potential to be a householdscalerenewableenergysolutionwhilereducingenvironmentalpollution.